FREE VIBRATION ANALYSIS OF MINDLIN PLATES WITH EXPONENTIALLY VARYING THICKNESS - TUTAK, B; AKSU, G (Inst Sound Vibration Research, 1994)
[Abstract Not Available]
5th International Conference on Recent Advances in Structural Dynamics -- JUL 18-21, 1994 -- UNIV SOUTHAMPTON, INST SOUND & VIBRAT RES, SOUTHAMPTON, ENGLAND